A new species of amphipod, Photis inornatus sp. nov. (Corophiidea, Photidae) from a ‘Haploops community’ in Brittany - Myers, Alan A.; Rigolet, Carine; Thiébaut, Eric; Dubois, Stanislas F. (Zootaxa, 2012)
A new species of Photis, P. inornatus sp. nov., is described and figured from a Haploops community between 20 and 35m depth in shallow waters from South Brittany, in the bay of Concarneau, northernmost part of the Bay of Biscay. Thisspecies was consistently found in macrobenthic samples extracted from the muddy Haploops community but not in sur-rounding muddy environment. An updated identification key is provided for European Atlantic and Mediterranean species of Photis.